1994
DOI: 10.2166/wst.1994.0389
|View full text |Cite
|
Sign up to set email alerts
|

Neutralisation of Acid Water in the Chemical Industry with Limestone

Abstract: The replacement of lime with limestone for the neutralisation of acid water was investigated through batch and semi-continuous studies. A fluidised-bed reactor with multiple stages of increasing diameters is preferred for the limestone neutralisation process as it allows fluidisation of the bigger particles but also prevents washout of the smaller particles in the case where ungraded particle size limestone is used. It was determined that the rate of neutralisation is influenced by the particle size of limesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The fluidised-bed limestone neutralisation process has been developed to neutralise free acid and remove Fe (II) and Al (III) concomitantly (Maree et al 1992;du Plessis and Maree 1994;Maree and du Plessis 1994;Maree 1994;Maree et al 1996 a,b). Previous studies showed that:…”
Section: Introductionmentioning
confidence: 99%
“…The fluidised-bed limestone neutralisation process has been developed to neutralise free acid and remove Fe (II) and Al (III) concomitantly (Maree et al 1992;du Plessis and Maree 1994;Maree and du Plessis 1994;Maree 1994;Maree et al 1996 a,b). Previous studies showed that:…”
Section: Introductionmentioning
confidence: 99%
“…Biooxidation employs microorganisms, such as, Acidithiobacilli species in the oxidation of the sulphide minerals in the concentrate at pH between 1.2 and 1.8 at temperature between 42 and 45 o C. Upon completion of biotransformation of the sulphide concentrate, liquid and solid separation is carried out in a counter current decantation (CCD) circuit. The effluent generated is, therefore, laden with arsenic, sulphate and other base metals ions and these ions must be removed from the effluent before impoundment in any resipotory (Du Plessis and Maree, 1994). The removal of arsenic in a form that is stable is important because arsenic is carcinogenic and can be mobilised into the geoenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the neutalisation reaction is very fast, a situation that results in formation of unstable precipitate such as calcium arsenate (Pantuzzo and Ciminelli, 2010;Zhu et al, 2006;Swash and Monhemius, 1994). To reduce the reaction rate, calcium carbonate has been used in addition to lime in a-two stage neutralisation process of the bio- (Hamester et al, 2012, Bologo et al, 2009Maree and du Plessis, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Its main advantage over lime is its lower price, and the production of smaller sludge (6). Its main advantage over lime is its lower price, and the production of smaller sludge (6).…”
Section: Introductionmentioning
confidence: 99%